CHARACTERISTICS OF MASCULINITY PRESENTED BY JACKIE ELLIOT AND ITS CHARACTERIZATION IN BILLY ELLIOT FILM - ., Widiya; Murtiningrum, Afina (Jurnal Ilmiah Sultan Agung, 2024)
This study aims to determine the characteristics of masculinity of Jackie Elliot and the characterization in the film Billy Elliot. This study focuses on the character Jackie Elliot who has masculinity characteristics in the film Billy Elliot. It explains and analyze the concept of masculinity using Janet Saltzman Chafetz and Edward Jones’s theory of characterization. This study used a descriptive qualitative method. The primary data used in this study were the movie script of Billy Elliot film and the movie of Billy Elliot film. The secondary data used in this study were journals, book, and previous research. The steps used to collect the data were watching the film, reading the movie script, identifying the data, classifying the data, and reducing the data. This study finds the masculinity and characteristics of the character Jackie Elliot. Based on the references used in this study Jackie Elliot has six of the seven characteristics of masculinity, namely physical, function of the male, emotion, intelligence, interpersonal, and other personal characteristics. Jackie Elliot’s characterization can be found in four of five ways, characterization through appearance, characterization through dialogue, characterization through internal action, and characterization through reactions of other characters. Keywords: Characteristics, Masculinity, Jackie Elliot, Characterization, Billy Elliot Film